2016
DOI: 10.1364/ol.41.004995
|View full text |Cite
|
Sign up to set email alerts
|

Compact all-fiber figure-9 dissipative soliton resonance mode-locked double-clad Er:Yb laser

Abstract: The first demonstration of a compact all-fiber figure-9 double-clad erbium-ytterbium laser working in the dissipative soliton resonance (DSR) regime is presented. Mode-locking was achieved using a nonlinear amplifying loop (NALM) resonator configuration. The laser was assembled with an additional 475 m long spool of SMF28 fiber in the NALM loop in order to obtain large net-anomalous cavity dispersion (-10.4  ps2), and therefore ensure that DSR would be the dominant mode-locking mechanism. At maximum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(32 citation statements)
references
References 30 publications
2
30
0
Order By: Relevance
“…The measured autocorrelation traces presented in Fig. 4 show flat signals, which confirm that the pulses were not noise-like pulses [10,15].…”
Section: Experiments and Discussionsupporting
confidence: 55%
“…The measured autocorrelation traces presented in Fig. 4 show flat signals, which confirm that the pulses were not noise-like pulses [10,15].…”
Section: Experiments and Discussionsupporting
confidence: 55%
“…It has been shown experimentally that high non-linearity plays an important role in the widening pulse [7]. Recently, dissipative soliton square pulses were demonstrated in a novel figure-9 fiber laser configuration with a pulse duration recorded around 455ns and an output energy per pulse about 2.3µJ [8].…”
Section: Abstract-dissipative Soliton Resonance (Dsr) Is a Soliton Fomentioning
confidence: 99%
“…It has been shown experimentally that high non-linearity plays an important role in the widening pulse [7]. Recently, dissipative soliton square pulses were demonstrated in a novel figure-9 fiber laser configuration with a pulse duration recorded around 455ns and an output energy per pulse about 2.3µJ [8].In this letter, we present, in different configurations, an experimental study on achieving up to 10μJ pulse energy [4,9] for a square pulse operating in a dissipative soliton resonance region, with tunable width in a wide range.Since long fibre cavities were experimentally used in order to favour the generation of high energy square pulses under the DSR regime [10], we have built long cavities operating in an anomalous dispersion regime relaying on nonlinear polarization evolution and figureof-eight mode-locking mechanisms. The first demonstration consists in a simple all fibre ring cavity passively mode-locked through nonlinear polarization evolution.…”
mentioning
confidence: 99%
“…To date now, mode-locked square-wave pulse are generally generated based on the nonlinear amplifying loop mirror (NALM) technique [10][11][12], nonlinear polarization rotation (NPR) mechanism [13]. It is rarely reported that new materials are used as saturable absorbers to generate square-wave pulses due to the damage threshold of these materials is generally low, they cannot withstand large energy pulses.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristic of the pulse is that the energy pulse could increase indefinitely as pump power increases while simultaneously the amplitude remains constant, which is represented in the time domain as flat-top or square-wave pulse. This idea attracted a lot of researches, which led to a large number of published research results and improved the pulse energy to the level of μJ [7-9].To date now, mode-locked square-wave pulse are generally generated based on the nonlinear amplifying loop mirror (NALM) technique [10][11][12], nonlinear polarization rotation (NPR) mechanism [13]. It is rarely reported that new materials are used as saturable absorbers to generate square-wave pulses due to the damage threshold of these materials is generally low, they cannot withstand large energy pulses.…”
mentioning
confidence: 99%